Descriptive study of breast problems in women who present to the general outpatient of a tertiary hospital in eastern region of Nepal - Giri, Rajani; Bhandari, R; Mahato, I; Poudel, M; Kumari, S; Yadav, AK (Health Renaissance, 2013)
Background: Breast problems are common among female patient attending general outpatient. Although the problem is expected to have significant morbidity, patients usually hide or present late for breast related problems in Nepal. Objective: To measure the pattern of breast diseases and its frequency and distribution in different age groups among patients attending general outpatient department at BPKIHS, Nepal. Methods: A crosssectional study was conducted in general outpatient department (GOPD) of B.P.Koirala Institute of Health Sciences (BPKIHS) during a period of six months. Women of all age groups presenting with breast problem were included. Clinical assessment, fine needle aspiration cytology (FNAC) and radiology were done. Mammography being unavailable at the hospital, ultrasonography was the preferred method of imaging. Results: Hundred cases of breast diseases were assessed. The benign breast disease (BBD) was the commonest finding (96%). Among BBD, fibroadenoma was the commonest (32%) followed by breast abscess (26%) and mastalgia (22%) including cyclic and non cyclic. The common age groups of involvement were 30-39 years for fibroadenoma, 20-29 years for breast abscess, 30-39 years for cyclic mastalgia, 40- 49 years for non cyclic mastalgia and 70-79 years for breast cancer. Conclusion: BBD is the most common breast problem in women. Among BBD, fibroadenoma was the most common. Health Renaissance, January-April 2013; Vol. 11 No.1; 33-37 DOI: http://dx.doi.org/10.3126/hren.v11i1.7599